Alkyl sulfone bridged phosphorus flame-retardants for polypropylene. (15th February 2021) - Nazir, Rashid; Gooneie, Ali; Lehner, Sandro; Jovic, Milijana; Rupper, Patrick; Ott, Noemie; Hufenus, Rudolf; Gaan, Sabyasachi
Abstract: Three novel alkyl sulfone bridged phosphorus (P) compounds namely 6, 6′-(sulfonylbis(ethane-2, 1-diyl))bis(dibenzo[c, e][1, 2]oxaphosphinine 6-oxide) (SEDOPO), sulfonylbis(ethane-2, 1-diyl))bis(diphenylphosphine oxide) (SEDPPO), and tetraphenyl (sulfonyl bis(ethane-2, 1-diyl)) bis(phosphonate) (SEDPP) (i.e. phosphine oxide, phosphinate and phosphonate, respectively) were synthesized via a Michael addition reaction with good yields (≥ 85%) at a 200-g scale. They exhibited thermal stability above 250 °C, which allowed them to be melt-processed with polypropylene (PP) and formed into thin films ( 0.6 mm). Rheological measurements of the PP blends exhibited a typical shear thinning behavior and provided evidence for the synthesized compound's thermo-oxidative stabilizing effect. This was also confirmed by thermal analysis showing that the thermo-oxidative stability of PP-SEDOPO and PP-SEDPPO blends was higher ( 25 °C) than the blank PP; however, PP-SEDPP had a smaller impact. Small scale fire tests of the PP-FR blends confirmed the flame retardant efficacy of the new P-compounds. Cone calorimetry on PP-SEDOPO blends showed a reduction in the heat release rate (HRR) ( 48%) compared to blank PP. Further thermal and evolved gas analysis of the PP blends confirmed that the new P-compounds are primarily active in the gas-phase. Graphical abstract: Unlabelled Image Highlights: Meltable Alkyl sulfone bridged compounds were synthesized in a simplified method. They have thermal stability > 250 °C and melt-processable with polypropylene. The incorporation of FR in PP achieves a significant reduction in heat release rates ( 48%). Incorporation of alkyl sulfone bridged compound improve the thermo-oxidative stability of polypropylene. The polypropylene passes vertical burning test with low phosphorus content (1%).